Research on the management of the system construction of National parks with China characteristics: Evidence from policy texts - Jun-Hui Li; Hai-Tao Yu; Wen-Lie Chen; Yuan Wang (PLoS ONE, 2026)
Quantitative evaluation of China’s national park policy texts is an important window to understand its national park governance logic, top-level design of ecological protection, and future practice. This study focuses on three key areas: the central government’s top-level design of national parks, local government responses, and the heterogeneity of these responses. By analyzing 77 national park policies in China, the following conclusions are drawn: (1) The central government’s vision for the national park system emphasizes ecological conservation and sustainable livelihoods for indigenous communities. (2) There are significant differences between local governments in the specific implementation of national park policies. (3) The first five established national parks show significant differences in terms of conservation objectives, integrated management practices, spatial planning, industrial development directions. Its findings offer valuable inspiration for developing countries to establish national parks protection systems and provide direct reference for global biodiversity governance. And it will also play a key role in achieving the action-oriented global goals of Kunming-Montreal Global Biodiversity Framework.